Students' motivational orientations and their study well-being across different disciplines - Laitinen, Satu; Laakkonen, Eero; Tuominen, Tiina; Kaukiainen, Ari (Elsevier BV, 2025)
The study aimed to analyze motivational orientation among 1st to 5th year students from different disciplines. Students were clustered according to motivation scores, and the relationships between the disciplines and the students' perceptions of their study well-being were examined. The study was conducted with two cohorts from a sample of 2347 students. Students completed a questionnaire exploring motivational orientation and study well-being, including engagement, burnout, and self-compassion. The latent profile approach facilitated examination of motivational orientation profiles and the extent to which perceived study well-being was related to motivational group identification. From the results, the students were classified into three motivation groups: mastery-oriented, moderation-oriented, and avoidance-oriented. The seven faculties showed significant differences relative to the motivational profile groups. Multinomial logistic regression analysis revealed differences between motivation group variables and study well-being factors.